PENGGUNAAN TEKNIK HYPNOTEACHING UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN DI TK AL–IZHAR SCHOOL KECAMATAN TAMPAN KOTA PEKANBARU - Sartika Sartika; Zulkifli Zulkifli; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Children listening ability in kindergarten Al-Izhar School Tampan District Pekanbaru City is still in the category of MB. The aims of this study to determine whether the use of hypnoteaching techniques can improve children listening ability, to find out how the children listening ability in using hypnoteaching techniques, to find out how high improvement the children listening ability in using hypnoteaching techniques. This research is a classroom action research that conducted with 2 cycles. Each cycle consists of 3 meetings. Subjects in this study were children aged 5-6 years, around to 16 people. Data collection techniques in this study using observation and documentation. The results show that hypnoteaching techniques can improve the listening skills of children. Results on pre cycles listening capability of 38.28% then in Cycle I increased to 50,64%. In Cycle II the listening ability increased to 70.83%.Keywords: Listening Ability, Hypnoteaching Techniques, Early Childhood